A new potential therapeutic remedy against Aeromonas hydrophila infection in rainbow trout (Oncorhynchus mykiss) using tetra, Cotinus coggygria - Bilen, Soner; Elbeshti, Housam Taher Abdul Ghani (Wiley, 2019)
AbstractDifferent antibiotic‐based drugs are being used for the treatment of Aeromonas hydrophila infection in rainbow trout, and several studies emphasize the use of medicinal plants as immunostimulants for prophylactic measure against Aeromoniasis disease. However, therapeutic effects of aqueous methanolic extracts of tetra (Cotinus coggygria) against A. hydrophila in rainbow trout were not investigated. Four different concentrations of tetra extract (0 [control], 4, 8 and 12 mg/100 µl) and also two different positive control groups (florfenicol and doxycycline antibiotics) were administered orally using feeding needles to individual rainbow trout, Oncorhynchus mykiss of all experimental groups twice a day after intramuscular inoculation of A. hydrophila. The study period was for 10 days. On 0th, 3rd, 7th and 10th day, blood and tissues were collected from the fish and changes in humoral immune responses, haematology and immune‐related gene expressions were determined. In the study, superoxide radical production was decreased generally in all experimental groups except in 12 mg tetra and florfenicol treatments compared to control (p < .05). Lysozyme activity was generally decreased (p < .05), or no differences were observed in all experimental groups compared to the control. Myeloperoxidase activity was significantly increased in florfenicol‐treated fish group on 7th day (p < .05). Generally, myeloperoxidase activity showed an increase in almost all tetra‐treated groups. Haematological parameters increased but were not significantly high enough in treatments. Almost all immune‐related gene expressions were significantly enhanced on 3rd and 10th day of the study. Survival rate of 53.33% was found in control group. There were no significant differences in survival between control and 4 mg tetra‐treated group (p > .05). All the other groups' survival rate was significantly increased compared to control. The highest survival rate was found in florfenicol group (80%). In 12 mg tetra‐, doxycycline‐ and 8 mg tetra‐treated groups, survival rate was recorded as 74.44%, 70% and 70%, respectively. Our results suggest that tetra methanolic extract is an effective therapeutic remedy against A. hydrophila infection in rainbow trout at the dose of 24 mg/32.34 g body weight/day.
Keywords: Fish Proteins; Hematologic Tests; Plant Extracts; Anacardiaceae; Gene Expression; Animal Feed; Aeromonas hydrophila; Anti-Bacterial Agents; Diet; Immunity, Humoral; Fish Diseases; Oncorhynchus mykiss; Animals; Gram-Negative Bacterial Infections; 3. Good health